Influence of tool surface on wall sliding of polymer melts. (2016) - Zitzenbacher, G.; Bayer, T.; Huang, Z.
The influence of the tool surface on the wall sliding behaviour of a polypropylene pipe grade and a high density polyethylene blow moulding grade is investigated in this paper. A ground and a polished tool steel surface, in addition to titanium nitride (TiN), titanium aluminium nitride (TiAlN), diamond like carbon (DLC) and polytetrafluoroethylene (PTFE) coatings are evaluated using a high pressure capillary rheometer combined with a rheological slit die. It was observed that especially the surface roughness, the polarity and the type of chemical bonds of the tool material affect wall sliding. A higher surface roughness leads to a decrease in the wall sliding velocity of the investigated polypropylene and to complete wall adhering of the high density polyethylene. TiN reduces the wall sliding of polypropylene at higher temperatures, while TiAlN has a similar effect as higher surface roughness, whereby DLC causes only poor wall sliding. It was also observed that tool materials which reduce wall sliding also decrease the critical wall shear stress for the onset of sharkskin of the investigated polypropylene.